(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This research explores the nuanced connection between visual and auditory art, with a specific focus on the thematic element of “animals in the arts.” The study is driven by three primary objectives: to elucidate art interpretation among individuals lacking formal art training, examine the alignment of visuals with corresponding music, and compare responses between musicians and non-musicians. Additionally, the study delves into participants’ assessments of artistic performances created by animals. Participants were adults (N=25, aged 30-74, mean 51.8), devoid of formal visual art training, of whom 11 possess an extensive musical background. In individual sessions, participants interpreted animal imagery, matched images with corresponding music, and evaluated artistic performances by animals. A pivotal finding underscores that exposure to animal-inspired music notably enhances initial visual perceptions—a phenomenon termed the ‘Enrichment Effect,’ more pronounced among non-musicians. The study advocates for a comprehensive, integrated approach to art-music education.